"He'd Tell Me I was Frigid and Ugly and Force me to Have Sex with Him Anyway": Women's Experiences of Co-Occurring Sexual Violence and Psychological Abuse in Heterosexual Relationships. Issue 1 (January 2023) - Tarzia, Laura; Hegarty, Kelsey
Intimate partner sexual violence (IPSV) is a common yet hidden form of violence. It is primarily perpetrated against women by their male partners and is associated with a range of serious mental and physical health outcomes. Despite these harms, it is chronically under-researched. In particular, the overlaps between IPSV and psychological abuse in relationships are poorly understood. Extant literature has focused primarily on the relationship between IPSV and physical violence, neglecting the fact that IPSV often involves verbal or emotional coercion, threats or blackmail rather than the use of 'force'. In this paper, we draw on reflexive thematic analysis of qualitative interviews with n = 38 victim/survivors of IPSV to explore how they understood the relationship between sexual and psychological abuse in their heterosexual relationships. Four themes were developed from this analysis: 1. I felt like I couldn't say Nno'; 2. I felt degraded and worthless; 3. Letting me know who's boss; and 4. Making me feel crazy. These themes broadly correspond to four distinct patterns or interactions between IPSV and psychological abuse. Our findings strongly suggest that the relationship between sexual and psychological abuse in relationships is far more complex than previous research would indicate. Psychological abuse is not simply a tool to obtain sex and sexual violence is not only used as a mechanism of psychological control. Instead, the two forms of abuse interact in ways that can be unidirectional, bi-directional or simultaneous to develop and maintain an environment of fear and control and erode women's self-worth.